L LâANALYSE DE LA PRÃPARATION DES ÃTUDIANTS DU HUITIÃME SEMESTRE DU DÃPARTEMENT DE LâENSEIGNEMENT DES LANGUES SECTION FRANÃAISE DE LâUNIVERSITÃ DâÃTAT SEMARANG Ã SUIVRE LE DELF B1 - Istiani, Putri; W, Diah Vitri; Agustiningrum, Tri Eko (Didacticofrancia: Journal Didactique du FLE, 2016)
The research aims to know the readiness of eighth semesterâs students of french education ofSemarang State University in taking the test DELF B1. It is a descriptive research. The variable in this research is the readiness of eighth semesterâs students of french education of Semarang State University in taking the test DELF B1. The respondents were the eighth semesterâsstudents of french education of Semarang State University. This research used documentation method and questionnaire method. The validity is construct validity. The reliability usedRulon formula. The data is analyzed by percentage formula. The result shows that generally,the eighth semesterâs students of french education of Semarang State University have a goodreadiness in following the test DELF B1. This is indicated that 90% students in ready categoryand very ready category. But, in an aspect psychological 65% students are not ready to takethe test DELF B1.